Industrial training report: MH Milk Sdn Bhd - Muhammad Yushri, Muhammad Izzan Syahmi (Universiti Teknologi MARA, Perlis, 2024)
Since its establishment in 2016, MH Milk Sdn Bhd has grown to become Pulau Pinang, Malaysia's top distributor of Farm Fresh products. The company, led by Mohd Helmi bin Ahmad Adnan, has raised the bar for the dairy industry with its strategic vision, capable management, and dedication to quality. The goals of MH Milk are to establish Farm Fresh as the leading dairy product in Malaysia and to guarantee that all Malaysians have access to fresh milk. The company sells a variety of dairy products that have been processed to guarantee their safety, quality, and nutritional content. These products include pasteurised milk, UHT milk, coconut milk, and Farm Fresh Grow Powder. The company's savvy sales force, friendly workplace culture, and effective marketing strategy are all responsible for its success. But there are obstacles to overcome, like a lack of employees, insufficient promotion of other products, and problems with the products themselves. Partnerships, making the most of online presence, and focusing on health-conscious customers are all areas where they might expand. Risks from shifting governmental regulations, seasonal variations in demand, and competitive pressures need to be carefully controlled.